2014
DOI: 10.21608/jpp.2014.64551
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Studies on Sugar Pea: Effect of Plant Density and Some Natural Substances as Foliar Applications on Growth, Pod Yield and Quality.

Abstract: Two field experiments were conducted at Private Farm in EL-Salheya, SharKia Governorate, Egypt during winter seasons of 2012/2013 and 2013/2014 to study the effect of plant density and some foliar applications, i.e., moringa leaf extract (MLE), chitosan at 150 ppm and silicon at 200 ppm on vegetative growth, pod yield and quality of snow pea cultivars, i.e. "Compados and Snow Wind" and sugar snap pea cultivar "Sugar Snap". The results showed that Compados cultivar had more leaves and branches, longest plant he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Data revealed that chitosan or yeast extract ranked the most foliar application under natural soil salinity that produced the highest quality of seeds either by its maximum average of germinative and vegetative indices. That result was accordance with the importance of chitosan in improving the germination of seeds, vegetative and yield characters which optimize the character of seeds to be more resistant to stress and increase the availability of amino compounds (Chibu and Shibayama, 2001), uptake of water and essential nutrients (Guan et al, 2009), in addition of increase the accumulation of photosynthesis output compounds, total protein, total carbohydrates N, P and K in seeds (El-Sayed et al, 2014;Behboudi et al, 2018).…”
Section: Effect Of Foliar Applicationsupporting
confidence: 65%
“…Data revealed that chitosan or yeast extract ranked the most foliar application under natural soil salinity that produced the highest quality of seeds either by its maximum average of germinative and vegetative indices. That result was accordance with the importance of chitosan in improving the germination of seeds, vegetative and yield characters which optimize the character of seeds to be more resistant to stress and increase the availability of amino compounds (Chibu and Shibayama, 2001), uptake of water and essential nutrients (Guan et al, 2009), in addition of increase the accumulation of photosynthesis output compounds, total protein, total carbohydrates N, P and K in seeds (El-Sayed et al, 2014;Behboudi et al, 2018).…”
Section: Effect Of Foliar Applicationsupporting
confidence: 65%
“…Furthermore, Azra, (2011) and EL-Sayed et al (2014) found that spraying wheat, peas and tomato with M. oleifera extract increased all growth parameters, productivity and crop characteristics.…”
Section: Introdutionmentioning
confidence: 98%